2021
DOI: 10.3390/cells10051195
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation: Integrated Nervous Tissue Response through Intercellular Interactions at the “Whole System” Scale

Abstract: Different cell populations in the nervous tissue establish numerous, heterotypic interactions and perform specific, frequently intersecting activities devoted to the maintenance of homeostasis. Microglia and astrocytes, respectively the immune and the “housekeeper” cells of nervous tissue, play a key role in neurodegenerative diseases. Alterations of tissue homeostasis trigger neuroinflammation, a collective dynamic response of glial cells. Reactive astrocytes and microglia express various functional phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 173 publications
(235 reference statements)
0
21
0
Order By: Relevance
“…Thus, it is possible that mild neuronal inflammation may provide some early protection. On the other hand, as disease etiology progresses, an association with neuroinflammatory markers, including C-reactive protein (CRP), triggering receptor expressed on myeloid cells 2 (TREM2), intercellular adhesion molecule 1 (ICAM1), IFNs, and the IL-1 family, is typically reported ( 157 160 ).…”
Section: Biological Aging Hallmarks Of Cognitive Decline and Adrdmentioning
confidence: 99%
“…Thus, it is possible that mild neuronal inflammation may provide some early protection. On the other hand, as disease etiology progresses, an association with neuroinflammatory markers, including C-reactive protein (CRP), triggering receptor expressed on myeloid cells 2 (TREM2), intercellular adhesion molecule 1 (ICAM1), IFNs, and the IL-1 family, is typically reported ( 157 160 ).…”
Section: Biological Aging Hallmarks Of Cognitive Decline and Adrdmentioning
confidence: 99%
“…Under pathophysiological conditions, activated microglia may differentiate into a continuum of states between phenotypically polarized M1 and M2 states. M1 microglia, whose polarization prevails in neurodegenerative diseases, exert neurotoxic effects and produce pro-inflammatory cytokines and chemokines that maintain inflammatory processes, whereas M2 microglia are neuroprotective, produce anti-inflammatory cytokines and terminate inflammation, contributing to tissue repair [58,59]. The most important pro-inflammatory and cytotoxic mediators produced by M1 microglial cells are cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-1 and IL-6, and inhibition of their production may be an important factor for reducing neuronal damage.…”
Section: Neuroinflammation In Neurodegenerative Diseases: the Role Of Nf-κb Pathwaymentioning
confidence: 99%
“…Previous studies reported that chronic inflammatory response induced astrocytic and microglial activation in the hippocampus. 31 , 32 In this study, it was found that abdominal exploratory laparotomy led to a significant increase in the intensity of GFAP (vs sham, P <0.0001; Figure 4A and B ) and Iba1 (vs sham, P <0.0001; Figure 4D and E ), while VRT-043198 administration partially reversed these changes (vs AEL, P <0.0001 for GFAP; vs AEL, P =0.0002 for Iba1; Figure 4A, B, D and E ). In the present study, A1-type astrocytes indicated by C3 complement 33 and M1-type microglia indicated by CD86 34 were selected as biomarkers of inflammatory response in the late post-surgical stage.…”
Section: Resultsmentioning
confidence: 99%